Analysis of Cafe Marketing Strategy Using SWOT Method on Omah Bonsari - Ailsa Dahnaira Wachid; Iriani Iriani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Omah Bonsari is a cafe with industrial feel located in Tuban, East Java. The development of the trend of drinking coffee increases every year which causes many cafes to appear in various regions, including Tuban. This cafe does not yet have a marketing strategy to be able to compete with its competitors. Marketing strategy is one of the important aspects for a business to run well. This study aims to formulate a cafe marketing strategy that can be applied by Omah Bonsari. The method used is the SWOT method which analyzes the cafe's internal and external factors, namely Strength, Weakness, Opportunities, and Threats. Determination of the weight and rating of cafe factors using IFAS and EFAS matrices. The results of the weighting score are used to determine the position of the cafe compared to competitors and alternative strategies that can be applied with the help of the grand strategy. Alternative strategies are prepared based on the SWOT matrix. The internal factor weighting score is 3.0917 and the external factor is 2.7964. Based on the grand strategy, the position of Omah Bonsari cafe is in quadrant I, which means it can apply an aggressive strategy. The strategy that can be applied by Omah Bonsari is the strength and opportunities strategy as a marketing strategy in order to compete with competitors.